Chemotactic Activity on Human Neutrophils to Streptococcus mutans - Tetiana Haniastuti (Faculty of Dentistry, Universitas Indonesia, 2013)
Objective: The aim of this study was to evaluate chemotactic activity o neutrophil to S. mutans. Chemotaxis assay was performed in blind well chambers. Materials and Methods: Hanks balanced salt solution (HBSS) containing 106 S. mutans,  108 S. mutans, 10-8 M fMLP, or HBSS alone were placed in the lower wells of the chamber and covered with polycorbonate membrane filter. Neutrophils suspension (2x105 cells) was then placed in the upper compartment. After incubation for 60 mins at 37ºC in a humidified atmosphere with 5% CO2, the filters were removed and stained with Giemsa. Result: ANOVA revealed statistically significant differences among groups (p<0.05), indicating that S. mutans induced neutrophils chemotaxis. The number of neutrophils migration in response to 108 S. mutans and 106 S. mutans were signifiantly greater compared to fMLP (p<0.05). Conclusion: S. mutans may activate human neutrophils, resulting in the chemotaxis of the neutrophils. DOI: 10.14693/jdi.v16i2.99